How to measure the infinite mathematics with infinite and infinitesimal numbers - Benci, Vieri 1949- (World Scientific Publishing Company Pte Limited, 2019)
"This book contains an original introduction to the use of infinitesimal and infinite numbers, namely, the Alpha-Theory, which can be considered as an alternative approach to nonstandard analysis. The basic principles are presented in an elementary way by using the ordinary language of mathematics; this is to be contrasted with other presentations of nonstandard analysis where technical notions from logic are required since the beginning. Some applications are included and aimed at showing the power of the theory. The book also provides a comprehensive exposition of the Theory of Numerosity, a new way of counting (countable) infinite sets that maintains the ancient Euclid's Principle: "The whole is larger than its parts". The book is organized into five parts: Alpha-Calculus, Alpha-Theory, Applications, Foundations, and Numerosity Theory."--
Mode of access: World Wide Web. - System requirements: Adobe Acrobat Reader
Keywords: Nonstandard mathematical analysis; Calculus; Series, Infinite; Nichtarchimedische Analysis; Transfinite Zahl; Infinitesimalanalysis; Electronic books